Poetics Journal Digital Archive - Watten, Barrett; Hejinian, Lyn (Book collections on Project MUSE., 2015)
The highly influential Poetics Journal, whose ten issues were published between 1982 and 1998, contributed to the surge of interest in the practice of poetics. Edited by internationally recognized poet/critics Lyn Hejinian and Barrett Watten, the journal presents major conversations and debates, and invites readers to expand on the critical and creative engagements they represent. This archive re-presents virtually all the articles originally published in Poetics Journal, organized alphabetically by author and in searchable form. It features indexes by contributors, keywords, and volume. The writing that appeared in Poetics Journal reflects the development of a range of creative and critical approaches in avant-garde poetry and art over two decades. In making this content newly available, the editors hope to preserve the generative enthusiasm for innovative writing and art it represents, while encouraging new uses and contexts.